Wear Behavior and Surface Quality of Dental Bioactive Ions-Releasing Resins Under Simulated Chewing Conditions - Garcia, Isadora Martini; Balhaddad, Abdulrahman A.; Aljuboori, Noorhan; Ibrahim, Maria Salem; Mokeem, Lamia; Ogubunka, Akudo; Collares, Fabrício Mezzomo; Melo, Mary Anne Sampaio de (Frontiers in Oral Health, 2021)
Bioactive materials can potentially reduce caries lesions on the marginal sealed teeth by providing the release of critical ions (calcium, phosphate, and fluoride) for balance on hydroxyapatite crystals dissolution. Previous studies mostly focused on the ion-releasing behavior of bioactive materials. Little is known about their wear behavior sealed tooth under mastication. This study aimed to evaluate the wear behavior and surface quality of dental bioactive sealing resins under a simulated chewing model. Three bioactive resins (Activa, BioCoat, and Beautifil Flow-Plus) were investigated. A bioactive resin without bioactive agents was used as a control group. Each resin was applied to the occlusal surface of extracted molars and subjected to in vitro chewing simulation model. We have assessed the average surface roughness (Ra), maximum high of the profile (Rt), and maximum valley depth (Rv) before and after the chewing simulation model. The final material surface quality was also analyzed by Vicker’s hardness and scanning electron microscopy. Overall, all groups had increased wear after chewing simulation. Microscopy analysis revealed a similar pattern among the materials. The material with surface pre-reacted glass ionomer (Beautifil Flow-Plus) has not differed from control. However, the resin with polymeric microcapsules doped with bioactive agents (BioCoat) showed increased surface roughness parameters. Overall, bioactive resins may not have inferior wear behavior and surface quality compared to non-bioactive conventional resin. Keywords: polymers, dental caries, composite resins, calcium phosphate, fluorides.